Supply Chain Collaboration: An analysis of Haulier Forecast at Coca Cola Enterprises Ltd. - Vinnik, Irina (2008)
In todayâs business world customer satisfaction is a prerequisite for gaining competitive advantage. The ability to make accurate forecasts enables companies to meet customer needs at the right time and place. In order to improve their forecasts companies should recognize the role of collaboration with partners in the same supply chain. Collaboration facilitates synchronization of ideas and activities which enable participants to gain enormous benefits. Synchronisation can be achieved through sharing demand information between members of the supply chain which assist each of them in their operations planning. Instead of blindly forecasting direct customer orders, companies can have the knowledge of what to expect from other members of the supply chain through information sharing. Current practice of forecasting distribution requirements at a leading company in a soft drink market is going to be investigated which will enhance practical knowledge about the topic. If the company can obtain highly accurate forecasts it will lead to operational efficiency as well as better customer service. The analysis of the current approach at the company will be made as well as the ideas for its improvement.